2017
DOI: 10.1371/journal.pone.0183363
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the rifampicin resistance determining region (RRDR) of rpoB gene in multidrug resistance confirmed and newly diagnosed tuberculosis patients of Punjab, Pakistan

Abstract: Molecular screening of new patients suspected for TB could help in the effective control of TB in Pakistan as it is a high TB burden country. It will be informative to understand the prevalence of multi drug resistance for a better drug regimen management in this geographical area. The Rifampicin resistance determining region (RRDR) sequencing was used to identify mutations associated with drug resistance in DNA extracts from 130 known multidrug resistant (MDR) cultured strains and compared with mutations obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Between 85-90% of MTB has been reported that resistance to INH when it has the RIF resistance, and RIF resistance is regarded as a major marker of MDR [37]. The most mutations in rpoB gene concentrated on codon 516, which was inconsistent with relevant studies that codon 531 was more frequently [38][39][40]. However, a study in Brazil showed that codon 516 rpoB mutations exhibited a higher frequency than codon 531 mutations in Haarlen lineage [41].…”
Section: Discussionmentioning
confidence: 88%
“…Between 85-90% of MTB has been reported that resistance to INH when it has the RIF resistance, and RIF resistance is regarded as a major marker of MDR [37]. The most mutations in rpoB gene concentrated on codon 516, which was inconsistent with relevant studies that codon 531 was more frequently [38][39][40]. However, a study in Brazil showed that codon 516 rpoB mutations exhibited a higher frequency than codon 531 mutations in Haarlen lineage [41].…”
Section: Discussionmentioning
confidence: 88%
“…The mutation in the codon 531 stands out with higher frequency (61.8%), also found in other studies in the same state [ 22 , 29 ], in other regions of Brazil [ 30 , 31 ] and other countries [ 28 ]. The codon 516 in the rpo B gene was mutated in 16.8% of the isolates and 2.3% of them had single nucleotide exchange, other studies show a bigger mutation rate with SNP in this codon [ 30 , 32 ]. The codon 526 was mutated in 9.9% of the isolates, and similar results were found in MDR isolates from a nearby state [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is among the five highest-burden countries for RR cases, the most frequent mutations reported in RRDR regions were Ser450 (64.1%), Asp435 (13.3%) and His445 (12.7%). Earlier studies performed in Pakistan, were on small sample sizes, have also reported similar frequencies of changes at amino acid position 450 (52 and 56.4%), amino acid 435 (4.84% and 15%) and amino acid 445 (7 and 9.68%) [15,16]. Similar frequencies of mutations were reported by other countries in Asia, e.g., Ser450 mutation rates were reported in India (59%), China (60%) Nepal (58.7), and in Russia (66.6%).…”
Section: Discussionmentioning
confidence: 72%
“…In Swaziland 30% of RR cases, harbored mutations l outside the RRDR [35]. In Uganda, 18% (8/45), in China five mutations were detected outside the RRDR region [15,16]. Similarly, In Syria, one mutation was detected outside the RRDR region [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation